Absorptive/transmissive integrated frequency selective structure based on lumped resistance elements. Issue 3 (18th December 2019) - Wang, Aiai; Yan, Mingbao; Zhang, Jieqiu; Zhen, Lin; Wang, Jiafu; Qu, Shaobo
Abstract : In this study, an absorptive/transmissive integrated frequency selective surface based on lumped resistance elements is presented. This technique is based on loading the lumped resistance element on the square ring, cascading a special filter. A flat band response can be obtained from the two transmission poles in each transmission window. Simulated results show that the −0.5 dB bandwidths are about 1.61 GHz (3.63–5.24 GHz) and 3.35 GHz (14.22–17.56 GHz), respectively. There is a wide absorptive band between the two transmission windows. The −10 dB absorptive bandwidth is about 5.16 GHz (8.04–13.20 GHz). In addition, the design procedure and operating principle were given, and the result was further discussed. Furthermore, the proposed structure was fabricated and measured. The measured results demonstrated the high selectivity, good angular and polarisation stability of the proposed design.